2016
DOI: 10.7150/thno.15584
|View full text |Cite
|
Sign up to set email alerts
|

Lycorine Downregulates HMGB1 to Inhibit Autophagy and Enhances Bortezomib Activity in Multiple Myeloma

Abstract: Multiple myeloma (MM) is largely incurable and drug-resistant. Novel therapeutic approaches such as inhibiting autophagy or rational drug combinations are aimed to overcome this issue. In this study, we found that lycorine exhibits a promising anti-proliferative activity against MM in vitro and in vivo by inhibiting autophagy. We identified High mobility group box 1 (HMGB1), an important regulator of autophagy, as the most aberrantly expressed protein after lycorine treatment and as a critical mediator of lyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
70
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 66 publications
2
70
0
Order By: Relevance
“…Thus, we speculated that MALAT‐1 expression was involved in the pathophysiological process of MM, but the mechanisms deserve further investigation. It was found that HMGB1 highly expressed in myeloma cell lines than that in the B‐cells [Roy et al, ]. In our study, the expression of HMGB1 was also obviously increased in MM and its change tendency was similar with MALAT‐1.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Thus, we speculated that MALAT‐1 expression was involved in the pathophysiological process of MM, but the mechanisms deserve further investigation. It was found that HMGB1 highly expressed in myeloma cell lines than that in the B‐cells [Roy et al, ]. In our study, the expression of HMGB1 was also obviously increased in MM and its change tendency was similar with MALAT‐1.…”
Section: Discussionsupporting
confidence: 73%
“…Additionally, HMGB1 is also closely related to malignant hematological diseases, including lymphoma, myelodysplastic syndrome and MM. HMGB1 was overexpressed in MM and contributed to the growth and proliferation of myeloma cells [Roy et al, ]. The underlying mechanism of HMGB1 in the context of MM has not been clarified previously and needs further research and exploration.…”
mentioning
confidence: 99%
“…For instance, several studies have demonstrated that lycorine displays remarkable efficacy in the suppression of tumorigenesis (14,(19)(20)(21)(22)(23). However, the underlying mechanism involved remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Although the targets or mechanisms of lycorine are still undefined, the dominant biological effects and low cytotoxicity of lycorine render it as a potential clinical drug or lead. For instance, it has received much attention as a promising anticancer agent for bladder cancer, cervical cancer, leukemia, prostate cancer, and multiple myeloma (14,(19)(20)(21)(22)(23). However, the defined molecular mechanisms underlying lycorine-regulated suppression of tumorigenesis remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple myeloma (MM) is a kind of neoplastic plasma-cell disorder, characterized by the immersion of malignant plasma cells into bone marrow and still incurable [1,2]. The survival terms of patients with MM range from a few weeks to more than 10 years with the five-year survival rate of 40 %.…”
Section: Introductionmentioning
confidence: 99%